Kajian tentang Tingkat Ketidakhadiran Guru Sekolah Dasar dan Dampaknya terhadap Siswa - Philip Suprastowo (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2013)
This study is a research result that aims to find out: 1) the level of absenteeism of elementary school teachers; 2) profile of teacher’s absenteeism level in terms of aspects of education background, employment status, and certificate ownership; 3) causes of absenteeism factor; 4) impact of teacher’s absenteeism on school and student learning performance; and 5) efforts that has been done in minimizing teacher’s absenteeism. The study was conducted through a survey in 20 regencies/cities as samples that determined by cluster random sampling according to region distribution and a consideration on population distribution of number of teachers in that region. There were 168 primary schools involved in this study which determined randomly. Results of this study found that: 1) level of absenteeism in primary school teachers was relatively lower, that was 6.6%; 2) profile of absenteeism teachers were dominant in teachers with high school education, Civil Servants Status, and have certified; 3) the main cause of absenteeism of teachers was due to be assigned by school and other interests, including the needs of teachers with official permission; 4) the impact of teacher absenteeism was disruption on learning process, students deviant behavior, decrease in student achievement and school image; and 5) school has tried to overcome the problems by setting up and assigning substitute teachers/picket teachers/part-time teachers, and education office in regencies/cities preventively overcome the absenteeism of teachers by applying disciplinary rules and sanctions for absenteeism teachers consequently and consistently. ABSTRAK Kajian ini berupa hasil penelitian yang bertujuan untuk mengetahui: 1) tingkat ketidakhadiran guru SD; 2) profil tingkat ketidakhadiran guru ditinjau dari aspek latar belakang pendidikan, status kepegawaian, dan kepemilikan sertifikat; 3) faktor penyebab ketidakhadiran guru; 4) dampak ketidakhadiran guru terhadap sekolah dan prestasi belajar siswa; dan 5) upaya yang dilakukan untuk meminimalisir ketidakhadiran guru. Penelitian dilakukan melalui survei yang dilakukan di 20 kabupaten/kota sampel yang ditentukan secara cluster random sampling berdasarkan distribusi wilayah serta pertimbangan sebaran populasi jumlah guru di kabupaten/kota. Jumlah sekolah sebanyak 168 SDN ditentukan secara acak. Hasil kajian menemukan bahwa: 1) tingkat ketidakhadiran guru SD diketahui relatif rendah, yaitu 6,6%; 2) profil guru yang tidak hadir dominan pada guru berpendidikan sekolah menengah, berstatus Pegawai Negeri Sipil dan telah bersertifikat; 3) Penyebab utama ketidakhadiran guru karena ditugaskan untuk dinas dan berbagai kepentingan, serta keperluan guru dengan izin resmi; 4) Dampak ketidakhadiran guru yaitu terganggunya proses pembelajaran, perilaku siswa menyimpang, penurunan prestasi siswa, dan citra sekolah; dan 5) sekolah berupaya mengatasi agar pembelajaran tetap berjalan terutama dengan menyiapkan dan menugaskan guru pengganti/guru piket/guru honorer; serta dinas pendidikan kabupaten/kota secara preventif mengatasi ketidakhadiran guru dengan menerapkan peraturan disiplin dan sanksi terhadap guru secara konsekuen dan konsisten.